Islamic Banking; The Challenges and Reality in Malaysia: A Case Study on Bank Islam Malaysia Berhad - Bazliahi Ahmad Mahmud (Universiti Sains Islam Malaysia, 2022)
The main issue discussed in this academic project paper is regarding to the Islamic banking especially Bank Islam Malaysia Berhad (BIMB) which is the first Islamic banking in Malaysia. The study sought to determine the challenges faced by BIMB and its reality in Malaysia. The data gathering method has been used in order to get the data for this academic project. This method comprises of the library and documentary research. From the study, there are three possible challenges which BIMB has to face. There are from the economy, law and technology point of view. Finally, this study also shows that Islamic banking especially BIMB can dominate the financial system in Malaysia.